1996
DOI: 10.1063/1.471799
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the vapor–liquid equilibrium on the attractive intermolecular forces

Abstract: Integral equation theory for LennardJones fluids: The bridge function and applications to pure fluids and mixtures simulation and reference hypernetted chain equation results for structural, thermodynamic, and dielectric properties of polar heteronuclear diatomic fluids By means of fitting computer simulation data of 3D Lennard-Jones fluids, we present very simple analytical equations for the pressure and chemical potential as functions of the temperature and density. The standard thermodynamic requirement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The effect of short-rangedness or weakness of the attractive intermolecular forces on the phase behaviour has also been investigated for some model systems by simulations [9][10][11][12], the DFT of freezing, and other theories such as the van der Waals theory [13][14][15][16][17]. These studies have shown that the liquid-vapour coexistence ceases to occur if the attractive force is reduced to a critical strength depending on the nature of individual potential.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of short-rangedness or weakness of the attractive intermolecular forces on the phase behaviour has also been investigated for some model systems by simulations [9][10][11][12], the DFT of freezing, and other theories such as the van der Waals theory [13][14][15][16][17]. These studies have shown that the liquid-vapour coexistence ceases to occur if the attractive force is reduced to a critical strength depending on the nature of individual potential.…”
Section: Introductionmentioning
confidence: 99%